Wood Anatomy and Fibre Quality of the Least Known Timbers Belong to Actinidiaceae from Indonesia - Ratih Damayanti; Listya Mustika Dewi (Masyarakat Peneliti Kayu Indonesia, 2019)
Wood anatomy of 417 genera and 86 families belong to the major, minor, and the lesser known timbers of South- East Asia have been studied and described in 3 volumes of PROSEA books. This paper deals with timber species of the least known timbers, which have not been treated in the above mentioned PROSEA books, i.e.: Saurauia bracteosa, S. capitulata., and S. nudiflora from family Actinidiaceae. The objective of this study was to acquire descriptions of their anatomical features and evaluate the quality of their fibres for pulp and paper manufacture. Samples were provided by Xylarium Bogoriense, which were collected from various forest areas in Indonesia. Microscopic features observed comprise all features those listed by IAWA Committee in 1989. Fibre quality was determined based on their dimension and evaluated according to quality classification developed by FPRDC Bogor. The results indicate that identification of timber up to genera level is possible. Fibres of Saurauia spp. fall into quality class I, which means good for pulp and paper. The descriptions of anatomical features were presented. Sauraria have bright color, light yellow to light brown, fine texture, light, smooth to rather rough surface, and make it suitable to substitute ramin (Gonystylus spp.)